Allergic Bronchopulmonary Aspergillosis in Asthma and Cystic Fibrosis. (7th March 2011) - Knutsen, Alan P.; Slavin, Raymond G.
Abstract : Allergic bronchopulmonary aspergillosis (ABPA) is a Th2 hypersensitivity lung disease in response to Aspergillus fumigatus that affects asthmatic and cystic fibrosis (CF) patients. Sensitization to A. fumigatus is common in both atopic asthmatic and CF patients, yet only 1-2% of asthmatic and 7–9% of CF patients develop ABPA. ABPA is characterized by wheezing and pulmonary infiltrates which may lead to pulmonary fibrosis and/or bronchiectasis. The inflammatory response is characterized by Th2 responses to Aspergillus allergens, increased serum IgE and eosinophilia. A number of genetic risks have recently been identified in the development of ABPA. These include HLA-DR and HLA-DQ, IL-4 receptor alpha chain ( IL-4RA ) polymorphisms, IL-10-1082GA promoter polymorphisms, surfactant protein A2 (SP-A2) polymorphisms, and cystic fibrosis transmembrane conductance regulator gene ( CFTR ) mutations. The studies indicate that ABPA patients are genetically at risk to develop skewed and heightened Th2 responses to A. fumigatus antigens. These genetic risk studies and their consequences of elevated biologic markers may aid in identifying asthmatic and CF patients who are at risk to the development of ABPA. Furthermore, these studies suggest that immune modulation with medications such as anti-IgE, anti-IL-4 and/or IL-13 monoclonal antibodies may be helpful in the treatment of ABPA.